EXPERIMENTAL STUDY OF REFRIGERANT REPLACEMENT FROM R-22 TO R-290 HYDROCARBON IN DOMESTIC AC - Arrad Ghani Safitra; Prima Dewi Permatasari; Teguh Hady Ariwibowo; Lohdy Diana; Nabila Haninda Az Zahra; Lovyta Putri Adianti (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
Most of the refrigerant used in split-type AC machines is HCFC type R-22, which can potentially damage the ozone layer and global warming. Musicool-22 is a trade name for the hydrocarbon refrigerant R-290, an alternative refrigerant that can replace R-22. Tests were carried out on the test equipment by comparing R-22 and Musicool-22 with the same variation of thermal load. Based on the test, the performance of the two working fluids can be determined by determining the coefficient of performance (COP) and comparing it with various cooling loads. In addition, it is proven that using Musicool-22 can save electrical energy and the power value of the compressor. The data measured are temperature, pressure, voltage, and electric current. Based on the results of calculations carried out by changing R-22 to Musicool-22, it shows that the COP value increases. The highest COP of R-22 is 2.45 at an 80-Watt load, and Musicool-22 is 4.21 at a 320-Watt load. The application of Musicool-22 can save electrical energy by 15.40%. Moreover, it saved electricity usage costs of IDR 44,450.53 per month.